Numerical Simulation on Frost of Cryogenic Finned-Tube Vaporizer Based on Fractal Theory - Chen Shuping; Yao Shuting; Xie Fushou; Han Hongyin (Zhileng xuebao)
A model of frost formation and growth on the cryogenic surface of finned-tube vaporizer was proposed based on Diffusion Limited Aggregation (DLA) model, and through controlling the times of program running, the simulation on the different stages of frost formation and growth on the cryogenic surface was carried out in this paper. Combined with frost formation and growth on the cryogenic surface obtained by experimental observations, the rationality of numerical simulation was verified from fractal dimension and frost layer density. The result shows that frost layer density decreases with the increase of thickness in the early frosting stage as initial frost dendrite constantly grows branch crystal, and the fractal dimension of frost layer on the cryogenic surface is larger than the fractal dimension of frost layer on the general cold surface. The frost growth on the cryogenic surface is more complex, and it has a bigger ability of filling space. This investigation is significant to further understand the frosting mechanism on the surface of cryogenic finned-tube vaporizer, explore the effective defrosting methods, and enhance heat transfer characteristics of the vaporizer.